Soil enzymatic activity as a soil health indicator for mango orchards under subtropical region - ADAK, TARUN; PANDEY, G. (Journal of Soil and Water Conservation, 2021)
The ecological significance of this study was to assess the enzymatic activities in 200 mango orchards located at subtropical region of Lucknow, UP, India. Soil biological activities were widely considered as an indicator for ecological processes undergoes dynamic changes. Keeping this in view, dehydrogenase (DHA) and fluorescein diacetate (FDA) was employed to indicate the status of these orchard ecologies from which 200 soil samples were collected from root zone depth (0-30 cm). Data showed lower activity of these enzymes; with majority falls below benchmark level; only 13.5 and 23.5% DHA and FDA were in higher category level of >1.01 Î¼g TPF g-1 h-1 and >251 Î¼g fluorescin g-1 h-1, respectively. Soil organic carbon falls only 28% in the category of >0.75%. Lower productivity of mango orchards was linked to lower soil enzymatic activities and associated characters. Growers could adopt better management practices to improve the condition of soil biological health.